Mobile based application design of wireless motion detection for home security - Al Fitri, M.R. (Institute of Electrical and Electronics Engineers Inc., 2019)
Smart home security becomes necessary given an increasing level of criminality. Home security needs certain innovation that utilize the advancement of computer technology. Current security system only focuses on giving a warning when and where incident occurs. This paper proposed an Internet of Thing (IoT) system to monitor a house remotely and timely manner using smartphone application. A mobile-based application of Wireless Motion Detection is designed to support home security. It uses a wireless point to multipoint technique for each accelerometer and node sensor that connect to a microcontroller. The reason of using a wireless network on this system is because it is real-time, simple on implementation, and flexible on installation. This system will be one of the practical home security solutions that efficient and effective because of the Android applications for monitoring motion detection conditions at home in real-time. Â© 2019 IEEE.